Wartime women rape: a means of moral attack and emasculation in Lynn Nottage's Ruined - Salih, Elaff Ganim; Jujar Singh, Hardev Kaur; Wan Yahya, Wan Roselezam (Australian International Academic Centre, 2016)
Women rape at warfare was considered a consequence of war in the social, literary and political world for a long period of time. Some criminals of rape escaped justice and others were persecuted on the basis that they were involved in mass rape because it was a natural consequence of war. But, women are targeted with rape in time of war because they are the symbolic representation of a culture, ethnicity, and the unifying fabric of their people and nation. The objective of this paper is to show that war rape is not a result of war; instead it is a means of human destruction through moral attack and emasculation. It aims to show that women rape in warfare is neither a misogynist act nor a sexual violence but it is a pre-planned weapon used strategically and systematically to fulfill certain political and military agenda. The study focuses on the sexual abuse of women in the Democratic Republic of Congo in time of war in Lynn Nottage’s Pulitzer Prize play, Ruined (2007). The study applies Jonathan Gottschall’s Strategic Rape theory, which highlights war rape as a pre-planned military strategy. The enemy emasculates men and attacks them morally by raping their women.Consequently, men’s failure to protect their women causes them to give up resistance, leave their lands and families because of shame and humiliation. The study concludes that women rape in time of war is a tactic followed by conquerors intentionally to facilitate and guarantee the achievement of certain pre-planned goals as was the case of mass rape in the DRC.